The effect of different anesthetics on tumor cytotoxicity by natural killer cells. (15th January 2017) - Tazawa, Kazumasa; Koutsogiannaki, Sophia; Chamberlain, Matthew; Yuki, Koichi
Graphical abstract: Highlights: LFA-1 is involved in NK cell-mediated conjugation, polarization and tumor cytotoxicity. Volatile anesthetics isoflurane and sevoflurane are LFA-1 inhibitors. Volatile anesthetics attenuated NK-cell mediated conjugation, polarization and cytotoxicity. Intravenous anesthetics did not affect these NK cell functions. Abstract: A number of retrospective studies have suggested that choice of anesthetic drugs during surgical tumor resection might affect tumor recurrence/metastasis, or outcome of patients. The recent study showed that volatile anesthetics-based general anesthesia was associated with the worse outcomes than intravenous anesthetics-based general anesthesia. However, the underlying mechanism is yet to be determined. Because natural killer (NK) cells are implicated as important immune cells for tumor recurrence/metastasis in the perioperative period, we examined the effect of different anesthetics on NK cell-mediated tumor cytotoxicity. Because adhesion molecule leukocyte function-associated antigen-1 (LFA-1) is functionally important in NK cells and is inhibited by commonly used volatile anesthetics isoflurane and sevoflurane, we hypothesized that these anesthetics would attenuate NK cell-mediated cytotoxicity. Using human NK cell line NK92-MI cells and tumor cell line K562 cells as a model system, we performed cytotoxicity, proliferation, conjugation and degranulation assays. Lytic granule polarization was also assessed. We showed that isoflurane, sevoflurane and LFA-1 inhibitor BIRT377 attenuated cytotoxicity, and reduced conjugation and polarization, but not degranulation of NK cells. Our data suggest that isoflurane and sevoflurane attenuated NK cell-mediated cytotoxicity at least partly by their LFA-1 inhibition in vitro. Whether or not isoflurane and sevoflurane attenuate NK cell-mediated tumor cytotoxicity in patients needs to be determined in the future.